Evaluation of Some Drought Tolerant M5 Rice Genotypes on Proline Content and Yield Components at Different Levels of Field Capacity - Raihanun, Siti; Sudharmawan, A.A.K.; Kisman, Kisman; Wangiyana, Wayan; Yakop, Uyek Malik (Journal of Science and Science Education, 2024)
Massive conversion of agricultural land, especially on wetlands, has resulted in declining rice productivity, so extending cultivation to drylands is considered appropriate. However, limited water availability is a major constraint that cannot be ruled out, so the procurement of drought-adaptive high-yielding varieties is considered to be the most effective solution. The purpose of this study was to evaluate drought-tolerant mutant genotypes based on proline content and yield component characters at various percentages of water availability. The experiment was arranged using a factorial complete randomized design, the first factor is drought stress consisting of 100% field capacity (K3), 66% (K2), 33% (K1) and the second factor is genotype consisting of inpago unram (P1), MD200-G13-3-11-5 (P2), MD300-G20-8-3-5 (P3), MD200-G24-17-10-8 (P4), MD300-G27-16-9-5 (P5). The observed characters consisted of proline content, flag leaf length, panicle length, filled grain weight and hollow grain weight. The results showed that MD300-G27-16-9-5 (P5) is a mutant plant that has the greatest potential to obtain drought-tolerant traits, although the level of proline produced is not as high as Inpago Unram (P1) and MD200-G24-17-10-8 (P4), but the consistency of adaptation shown by MD300-G27-16-9-5 (P5) when experiencing drought stress tends not to cause a significant decrease in all yield component characters, namely flag leaf length, panicle length, filled grain weight and unfilled grain weight